Student leadership training as a stress reduction strategy at a South African university - Mulenga, C.N.; Brouze, K.; Gardner-Lubbe, S. (South African Journal of Higher Education, 2016)
The role of student leaders at tertiary institutions is common practice. Student leaders participation in both academic and residence leadership roles provides an opportunity for skills development and also a source of income. The multiplicity of roles that residence leaders fulfill have been reported to be a source of stress and dissatisfaction which has had a negative effect on their academic performance. A descriptive research design using a self-report cross-sectional approach was used. The population was student leaders from 19 residence halls at a South African tertiary institution (n=184). Psychometric properties of measures used were consistent with previous studies. Significant positive correlations between role overload and role stress as well as training and role satisfaction were established. A negative relationship was established between training and role satisfaction. These findings are consistent with previous studies that reported training as an important factor in determining student leader satisfaction. Key words: Role stress; role overload; student leadership; training; role satisfaction; performance